The feasibility of using wind energy for rural populations lacking electric power in Brazil - Gabriel Filho, Luís Roberto Almeida [UNESP]; Sato, Karen Yumi [UNESP]; Putti, Fernando Ferrari [UNESP]; Seraphim, Odivaldo José [UNESP]; Gabriel, Camila Pires Cremasco [UNESP] (EIA Energy in Agriculture, 2013)
In the wake of current global image involving environmental impacts, the use of wind power has had a remarkable growth in recent years as a technique for generating electricity. In fact, it is a source featuring strong dissemination of technology which provides decrease in costs and a greater access to low-income electricity. PROINFA (Incentive Program for Alternative Energy Sources) promotes a greater diffusion of new technologies for power generation, in particular wind-produced. Due to such a scenario on the exploitation of such energy source, current analysis discusses strategies for the development of domestic wind technology and the implications for electricity-lacking rural areas. Analysis shows a similar behavior between rural populations lacking electricity and the amount of potential energy available in the region. It is expected that this assay will contribute towards the establishment of public policies for wind-energy parks on rural farms in the North and Northeast regions of Brazil.

Diante da atual imagem mundial, relacionado aos impactos ambientais, a utilização da energia eólica tem crescido muito nos últimos anos como forma de geradora de energia elétrica, já que trata de uma fonte com forte disseminação de tecnologia, o que proporciona não só uma diminuição dos custos que a utilizam, mas também um maior acesso da população de baixa renda à eletricidade. O PROINFA (Programa de Incentivo às Fontes de Alternativas de Energia Elétrica), por exemplo, promove uma maior difusão de novas tecnologias para a geração de energia elétrica, destacando-se principalmente a eólica. Diante do cenário de prospecção do uso desta fonte de energia, o presente estudo visa relacionar as estratégias para o desenvolvimento da tecnologia eólica nacional e as implicações em regiões rurais sem acesso à energia elétrica. Na análise do estudo, foi possível mostrar um comportamento semelhante entre a quantidade da população rural sem acesso a energia elétrica e a quantidade do potencial energético disponível por região, o que contribui para criação de possíveis políticas públicas visando a implementação de parques eólicos voltados ao meio rural das regiões Norte e Nordeste sejam efetivadas.
Análise da viabilidade da utilização da energia eólica pela população rural sem acesso à energia elétrica no Brasil
Keywords: Electricity; Brazilian northeast Region; Alternative energy sources; Eletricidade; Região Nordeste; Fontes alternativas de energia